TOURISM DEVELOPMENT DURING THE COVID-19 PANDEMIC IN BATU CITY, EAST JAVA - Mohammad Hidayaturrahman; Rillia Aisyah Haris; Imam Hidayat (JELAJAH: Journal of Tourism and Hospitality, 2022)
Covid-19, which has occurred since 2020 until now, has not only caused problems in the health sector, but also in the economy, including the tourism sector. This study was conducted to find out how the impact of the COVID-19 pandemic on the tourism sector in Batu City, East Java. In addition, this study was conducted to reveal how the strategy was carried out by the Batu City Government, East Java in developing the tourism sector after the COVID-19 pandemic. This study uses descriptive qualitative research methods, which describe the impact of the COVID-19 pandemic on the tourism sector in Batu City, East Java. In addition, it also described the efforts made by the Batu City Government to restore the tourism sector after being hit by the COVID-19 pandemic. Data collection in this study used a technical focus group discussion (FGD) with various parties involved in managing the tourism sector in Batu City, East Java. In addition, in-depth interviews and document searches were conducted. This research conducted in 2021 found that the impact of COVID-19 on the tourism sector of Batu City was quite large. There has been a decline of up to 75% in the number of tourists, which directly has an impact on the increase in the number of poor people. Efforts are being made by the Batu City Government, East Java to restore the tourism sector, by ensuring that tourism actors in Batu City implement health protocols, and sterilize tourism actors and visitors by intensively vaccinating. This is expected to create trust in tourists who want to return to visit Batu City.